Measuring outcomes in systemic lupus erythematosus clinical trials. (August 2011) - Strand, Vibeke; Chu, Alvina D
The recent approval of the biologic therapy, belimumab, for treatment of systemic lupus erythematosus (SLE) by the US FDA has shifted the developmental landscape of therapeutics for this autoimmune disease. Promising therapies are currently in development for the treatment of SLE, with trials designed to emphasize clinically relevant end points. This article will discuss outcome measures that have been utilized including disease activity indices, definitions of flare, measures of damage, global assessments of disease activity and measures of health-related quality of life. Application of these outcome measures in recent trials are highlighted as illustrative examples. Contributions to the recent success of randomized controlled trials in SLE have included use of evidence-based responder indices, clear definitions of treatment failure, predefined management strategies for use of immunosuppressive agents and corticosteroids, sufficient sample sizes and efforts to identify responsive patient populations. Each completed study in SLE promises to better inform trial design and offer further opportunities for success in a field with a continuing unmet therapeutic need.